In vitro evaluation of the apical seal of two different retrograde filling materials. (30th May 2016) - Benz, Korbinian; Markovic, Ljubisa; Jordan, R.A.; Novacek, Claudia; Jackowski, Jochen
Abstract: To determine whether the selection of retrograde filling material or the choice of instruments in root tip resection influences the seal of the retrograde root filling. Seventy‐two single‐rooted teeth were used. Root resection was performed using a Lindemann bone cutter, a Lindemann bone cutter with A‐shaped cutting design or a diamond‐coated bur. Retro‐cavities were prepared by piezo‐tips and filled with Super‐EBA or MTA. Teeth were made transparent and dye penetration was assessed. Teeth filled with MTA, irrespective of the resection instrument, showed no measurable dye penetration. All groups filled with Super‐EBA showed an apical leakage. There were no significant differences between the three groups filled with Super‐EBA ( P = 0.09). The comparison of MTA versus Super‐EBA showed significant superiority in apical seal in favour of MTA ( P < 0.0001). To use MTA as a retrograde filling material showed superior results in terms of the tightness of the apical seal as compared to Super‐EBA.